Effects of Treatment With Continuous Subcutaneous Insulin Infusion on Arterial Stiffness and Endothelial Glycocalyx Compared to MDI Intensification in Patients With Type 1 Diabetes: Improvement After a Six-Month Pump Treatment - Kountouri, Aikaterini (J Endocr Soc, 2021)
Patients with type 1 diabetes mellitus (T1DM) present signs of atherosclerosis and endothelial dysfunction earlier compared to healthy individuals. The evidence regarding the efficacy of continuous subcutaneous insulin infusion (CSII) in vascular function in T1DM are scarce. The aim of this study is to determine whether insulin intensification with CSII improves arterial stiffness and endothelial function in T1DM compared to multiple daily insulin (MDI) injections. Thirty patients with T1DM were included in our study. Fifteen patients with poor glycemic control were transitioned from MDI to CSII and were reviewed immediately prior (baseline) and six months after the initiation of CSII. Fifteen patients, matched for sex, age and glycemic control, remained on intensified treatment with MDI (control group). In all patients at each visit we measure a) Carotid-femoral PWV b) central systolic blood pressure (cSBP) c) perfused boundary region (PBR) of the sublingual arterial microvessels. Both groups had similar cardiovascular markers and HbA1c at baseline (p>0.05). After a six month treatment period, patients on CSII improved HbA1c (7.9±1.5% vs 7.35±0.7%, p<0.05), PBR (2.1±0.2 vs. 2±0.2 μm, p<0.05), PWV (7.5±0.3 vs. 7.4±1.1m/s, p<0,05) and cSBP (114.6±12.5 vs. 112±5.4 mmHg, p<0.05). There were no statistically significant differences in PBR (2±0.3 vs. 2±0.3 μm, p>0.05), PWV (8±2.3 vs. 8±1.9m/s, p>0.05) and cSBP (115±15.2 vs. 115.7±15.4 mmHg, p>0.05) in patients who remained on MDI, despite improvement of HbA1c (8±1.1% vs 7.36±0.8%, p<0.05). The use of CSII improves the thickness of endothelial glycocalyx and decreases arterial stiffness after six months treatment in patients with T1DM.